Kontribusi Literasi Keuangan, Inklusi Keuangan, dan Teknologi Finansial (Fintech) Pada Perilaku Manajemen Keuangan Mahasiswa - Alfina Yuniar Prastika; Ana Kadarningsih (MANAJEMEN, 2025)
Financial management behavior involves a person’s capability to handle daily financial for stability. This finding examines the components that influence the financial management behavior of Dian Nuswantoro University students. The study focuses on active students of Dian Nuswantoro University, with samples of FEB and FIK students in semesters 3-8 who use financial technology. Data were obtained through questionnaires and analysis was performed using SmartPLS version 3.2.9 tool. Examination shows that financial literacy and financial technology have a significant positive impact on financial management behavior, whereas financial inclusion does not have an students’ financial management behavior.